1987
DOI: 10.1128/jb.169.11.5279-5288.1987
|View full text |Cite
|
Sign up to set email alerts
|

Protein inclusions produced by the entomopathogenic bacterium Xenorhabdus nematophilus subsp. nematophilus

Abstract: The entomopathogenic bacterium Xenorhabdus nematophilus subsp. nematophilus produces two types of intracellular inclusion bodies during in vitro culture. Large cigar-shaped inclusions (designated type 1) and smaller ovoid inclusions (designated type 2) were purified from cell lysates, using differential centrifugation in discontinuous glycerol gradients and isopycnic density gradient centrifugation in sodium diatrizoate. The inclusions, composed almost exclusively of protein, are readily soluble at high and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Together, IP1 and IP2 represent Ͼ40% of the total cellular protein in stationary-phase cells (11). Immunodetection studies showed that IP1 was present in X. nematophila but not in other Xenorhabdus species (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Together, IP1 and IP2 represent Ͼ40% of the total cellular protein in stationary-phase cells (11). Immunodetection studies showed that IP1 was present in X. nematophila but not in other Xenorhabdus species (11).…”
mentioning
confidence: 99%
“…produce two distinct proteinaceous intracellular inclusions during stationary phase in culture and in insects (2,10,11). The sister taxon of Xenorhabdus, Photorhabdus, which engages in mutualistic associations with nematodes of the Heterorhabditidae family (1,7,13), also produces two morphologically distinct proteinaceous inclusion bodies (4,8).…”
mentioning
confidence: 99%
“…Recently, Clarke and Dowds (29) speculated that a secreted lipase is responsible for the insecticidal activity observed against Galleria mellonella. In addition to secreted factors, these bacteria are known to produce intracellular inclusion bodies similar to those produced by Bacillus thuringiensis (30,31). But unlike Bt endotoxin crystals they are not insecticidal and are thought to provide amino acid nutrients for the emerging nematodes (32).…”
mentioning
confidence: 99%
“…Upon nutrient depletion, the nematodes molt into third-instar nonfeeding larvae (32), take on X. luminescens symbionts, and emerge from the insect cadaver in search of new prey (16,32). Besides bioluminescence, X. luminescens produces several other interesting products: antibiotic substances (2,30,33), extracellular proteases (3,35), extracellular lipase (3,17), intracellular protein crystals (10), and a red pigment (33). The insect cadaver does not putrefy, presumably because the antibiotic activity inhibits the growth of other bacteria.…”
mentioning
confidence: 99%